Local Government as Linkage Actors: Domestic Sources of Foreign Policy in the United States - Grace Natali Simbolon; Leony Agustin; Ledy Krishonni Sianturi; Mirna Wahyuni (Austronesia Akademika, 2026)
This article examines local government as linkage actors in shaping the domestic sources of foreign policy in the United States. Although foreign policy is formally understood as the constitutional responsibility of the federal government, contemporary global challenges increasingly intersect with local governance responsibilities. Issues such as trade, foreign investment, climate change, migration, public health, infrastructure development, port governance, and transnational cooperation are experienced directly by states, cities, counties, and regional institutions. Using a qualitative descriptive approach based exclusively on secondary data, this study analyzes academic literature, policy documents, government publications, and institutional materials related to paradiplomacy, federalism, city diplomacy, subnational governance, and Foreign Policy Analysis. The findings show that local governments influence foreign policy not by replacing federal diplomatic authority, but by connecting local interests, regional development priorities, and community needs with broader national and international policy agendas. Local governments perform three major roles: institutional intermediaries that translate global issues into domestic policy responses; functional actors that participate in international arenas through economic, environmental, social, and urban networks; and policy mediators that provide implementation capacity, local knowledge, and policy feedback to federal institutions. The article argues that U.S. foreign policy should not be viewed only as a top-down process produced by national elites, but as a multi-level governance process shaped by interaction among federal, state, and local actors.